Stereotactic ablative radiotherapy for early-stage central lung tumors: status, challenges, and future considerations - Li, Ming; Zhan, Cheng (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
Different from general radiotherapy, stereotactic ablative radiation (SABR), also referred to as stereotactic body radiotherapy (SBRT), delivers very high radiation doses to restricted volumes using multiple, precisely-aimed radiotherapy beams, which has a better effect on survival and tumor control, and has gained substantial attention in recent years (1,2).